Evaluation of magnetic nanoparticles for magnetic fluid hyperthermia. (1st January 2019) - Lanier, Olivia L.; Korotych, Olena I.; Monsalve, Adam G.; Wable, Dayita; Savliwala, Shehaab; Grooms, Noa W. F.; Nacea, Christopher; Tuitt, Omani R.; Dobson, Jon
Abstract: Background: Magnetic nanoparticles (MNPs) generate heat when exposed to an alternating magnetic field. Consequently, MNPs are used for magnetic fluid hyperthermia (MFH) for cancer treatment, and have been shown to increase the efficacy of chemotherapy and/or radiation treatment in clinical trials. A downfall of current MFH treatment is the inability to deliver sufficient heat to the tumor due to: insufficient amounts of MNPs, unequal distribution of MNPs throughout the tumor, or heat loss to the surrounding environment. Objective: In this study, the objective was to identify MNPs with high heating efficiencies quantified by their specific absorption rate (SAR). Methods: A panel of 31 commercially available MNPs were evaluated for SAR in two different AMFs. Additionally, particle properties including iron content, hydrodynamic diameter, core diameter, magnetic diameter, magnetically dead layer thickness, and saturation mass magnetization were investigated. Results: High SAR MNPs were identified. For SAR calculations, the initial slope, corrected slope, and Box–Lucas methods were used and validated using a graphical residual analysis, and the Box–Lucas method was shown to be the most accurate. Other particle properties were identified and examined for correlations with SAR values. Positive correlations of particle properties with SAR were found, including a strong correlation for the magnetically dead layer thickness. Conclusions: This work identified high SAR MNPs for hyperthermia, and provides insight into properties which correlate with SAR which will be valuable for synthesis of next-generation MNPs. SAR calculation methods must be standardized, and this work provides an in-depth analysis of common calculation methods.